Kolomoki : settlement, ceremony, and status in the Deep South, A.D. 350 to 750 - Pluckhahn, Thomas J. (Thomas John), 1966- (Book collections on Project MUSE., 2003)
The first comprehensive and systematic investigation of a Woodland period ceremonial center. Kolomoki, one of the most impressive archaeological sites in the southeastern United States, includes at least nine large earthen mounds in the lower Chattahoochee River valley of southwest Georgia. The largest, Mound A, rises approximately 20 meters above the terrace that borders it. From its flat-topped summit, a visitor can survey the string of smaller mounds that form an arc to the south and west. Archaeological research had previously placed Kolomoki within the Mississippian period (ca. a.d. 1000-